210k views
2 votes
Solve the simultaneous linear equation: 6x-y=23
3y+6x=11​

User Chan Le
by
4.9k points

1 Answer

3 votes

Answer:

(
(10)/(3), - 3 )

Explanation:

Given the 2 equations

6x - y = 23 → (1)

3y + 6x = 11 → (2)

Subtracting (2) from (1) term by term eliminates the term in x

(6x - 6x) + (- y - 3y) = (23 - 11), that is

- 4y = 12 ( divide both sides by - 4 )

y = - 3

Substitute y = - 3 into either of the 2 equations and solve for x

Substituting in (1)

6x - (- 3) = 23

6x + 3 = 23 ( subtract 3 from both sides )

6x = 20 ( divide both sides by 20 )

x =
(20)/(6) =
(10)/(3)

Solution is (
(10)/(3), - 3 )

User Elveatles
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.